2021
DOI: 10.1002/agt2.140
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence: From mechanism to applications in biological imaging and therapy

Abstract: Chemiluminescence (CL) is an emission phenomenon induced by chemical reaction. Different from the photoluminescence, CL is free from external excitation source, which is expected to show great advantages such as higher signal-to-background ratio (SBR) in bioimaging, and deeper tissue penetration in photodynamic therapy (PDT). This review introduces the theoretical aspects of CL mechanism, such as classification, energy consideration and chemiexcited/photoexcited states. Application of CL in bioimaging is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 98 publications
0
42
0
Order By: Relevance
“…Moreover, more multiphoton excitation-activatable AIEgens as well as external light excitation-free theranostics including chemiexcitation-or ultrasound-activatable AIEgens are also needed for practical applications. 231,300 Secondly, the wide popularization of AIE NPs greatly advanced the development of theranostic systems featuring specificity and selectivity toward biomarkers by means of being facilely modified with targeting ligands on their surfaces. However, the already activated theranostic functions in the nanoaggregation process of AIEgens may cause damage to normal tissue once the off-target effect occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, more multiphoton excitation-activatable AIEgens as well as external light excitation-free theranostics including chemiexcitation-or ultrasound-activatable AIEgens are also needed for practical applications. 231,300 Secondly, the wide popularization of AIE NPs greatly advanced the development of theranostic systems featuring specificity and selectivity toward biomarkers by means of being facilely modified with targeting ligands on their surfaces. However, the already activated theranostic functions in the nanoaggregation process of AIEgens may cause damage to normal tissue once the off-target effect occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Different from traditional photoluminescence, chemiluminescence that relies on the energy release of chemical reaction rather than external light excitation is able to potentially and dramatically break the limitation of light source penetration depth, thus providing increased potential and opportunities for AIEgens in theranostic applications. 231 Liu et al reported a kind of AIEgen-based chemiluminescenceguided chemiexcited PDT system (C-TBD NPs) in 2017. 232 Here, the AIEgen TBD with efficient ROS generation capacity was employed as a PS, bis[2,4,5-trichloro-6-(pentyloxycarbonyl)-phenyl] oxalate (CPPO) was selected as a chemical excitation source to generate chemiluminescence by reacting with H 2 O 2 , soybean oil was introduced as the retarder to slow down the energy release rate and lengthen the half-lives of C-TBD NPs for the purpose of in vivo circulation.…”
Section: Two-photon Excitation-activatable Aiegensmentioning
confidence: 99%
“…38,39 The produced H 2 O 2 will further activate a peroxyoxalate CL reaction. [40][41][42] Specifically, H 2 O 2 will diffuse and react with the exposed DNPO at the damage site to produce peroxyacid ester, which is labile and will decompose spontaneously to generate carbon dioxide (CO 2 ) and release energy. The released energy can be absorbed by the preembedded dye to create an excited state, and since the dye in an excited state is unstable, it will luminesce to release the absorbed energy to return to its ground state.…”
Section: Self-reporting Mechanism In Underwater Hi-skinsmentioning
confidence: 99%
“…Chemiluminescence (CL) is a revolutionized imaging technique for in vivo monitoring of biospecies in which the signal contrast and sensitivity can be significantly increased since the light emission is initiated by a chemical reaction with minimal autofluorescence interference [ 128 , 129 , 130 , 131 ]. However, most traditional CL emitters are dependent on the generation of unstable and short-lived emitting species, making the photons release uncontrollable, and dynamic biological imaging difficult [ 132 , 133 ]. Guo and coworkers reported on a sequential dual-lock photoactivatable chemiluminescent AIE probe for bright optical imaging [ 134 ].…”
Section: Detection Of Reactive Oxygen Nitrogen Speciesmentioning
confidence: 99%